Nursing Care for Trauma Cases in Obstetrics : Literature Review - Wahyu Wulandari, Luckyta (D'Nursing and Health Journal (DNHJ), 2024)
Background: Basically, there are various kinds of hazards in the workplace that can threaten the health of workers and people around the company. Working environments that are often filled with dust, steam, gas and so on can disrupt productivity and harm health. This is what often causes respiratory disorders or can interfere with lung vital capacity values. Method: This study uses cross sectional study design. The analysis used in this study is a chi square test. Results: The majority of cement factory workers in the production section I are ≥ 40 years of age (94.1%), abnormal nutritional status (66.7%), have no history of lung disease (68.6%), smoking workers (58.8%), have a physical habit (66.7%) have a work life ≥ 5 years (92.2%), exposure to dust < 3 mg/m3 (80.4%). There is a relationship between smoking habits, exercise habits and working time with the lung functioning capacity of cement factory workers X. There is no relationship between age, nutritional status, history of lung disease, in cement plant workers company X 2019. Conclusion: Exposure to cement dust can potentially cause changes in lung function. This is more risky than other risk factors because cement can reach directly into the respiratory tract and trigger a response in the body.